Experience with a novel high frequency optical coherence tomography device for intracoronary imaging: a case series - Garin, Dorian; Cook, Stéphane; Togni, Mario; Meier, Pascal; Wenaweser, Peter; Puricel, Serban; Arroyo, Diego (Frontiers in Cardiovascular Medicine, 2024)
Introduction Intravascular imaging, especially optical coherence tomography (OCT), has significantly improved percutaneous coronary intervention (PCI), yet its routine clinical application faces challenges. This case series introduces the Gentuity® High-Frequency Optical Coherence Tomography (HF-OCT), a novel device designed to enhance intracoronary imaging with a significantly faster pullback and smaller catheter size, potentially offering enhanced navigability in complex lesions. We aimed to assess the image quality of Gentuity® HF-OCT in complex vessel conditions, as well as presenting a case series to illustrate the application of the device in various clinical scenarios. Methods In this case series, we included all patients who underwent intracoronary HF-OCT imaging at our center. The primary endpoint was image quality assessed by clear image length (CIL). Image quality was assessed in relation to (1) lesion severity assessed by minimum lumen area (MLA); (2) vessel size, differentiating between larger (diameter ≥ 4 mm) and smaller vessel segments; (3) pre- vs. post-PCI conditions, and (4) vessel tortuosity, categorized into none, moderate, and severe. Results Twenty-four HF-OCT runs from 14 patients were included. No significant differences in CIL were observed across lesion severity terciles (p = 0.449), between small and large vessel segments [mean CIL% difference 1.3%; confidence interval (CI), −9.3 to 11.8; p = 0.802], and pre- vs. post-PCI conditions (mean CIL difference −3.9 mm; CI, −14.0 to 6.1; p = 0.373). Vessel tortuosity significantly impacted image quality, with clear reductions in CIL observed in cases of moderate (74.8; CI, 73.5 to 76.0; vs. 63.9; CI, 56.2 to 71.5; p = 0.043) and severe tortuosity (74.8; CI, 73.5 to 76.0; vs. 65.0; CI, 62.1 to 67.9; p = 0.002) compared to vessels with no tortuosity. Overall, the HF-OCT demonstrated excellent catheter deliverability and crossability, with very satisfactory image quality and no significant adverse events. Conclusion The Gentuity® HF-OCT is a new OCT device capable of navigating both small- and large-diameter vessels, with similar image quality, but vessel tortuosity seems to have an impact on image quality. It appears to be as usable as conventional OCT for pre-PCI diagnosis and OCT-guided PCI, potentially bringing additional benefits in terms of deliverability, lesion crossover and ease of use in routine clinical practice.